TEACHING ENGLISH WORD FORMATION PROCESS USING ATTRACTIVE MEDIA - Vera Kristiana; Diana Sopha (Fakultas Sastra UMN AL Washliyah, 2023)
The purpose of this study is to explain the importance of learning media in delivering material in class. Learning media has a major role in the smooth running of the learning and teaching process. Especially during the Covid 19 pandemic yesterday, lecturers thought hard about how to maximize learning even in difficult situations. One solution is to find interesting and attractive learning media especially for teaching course material that students find difficult. One such material is about the process of word formation in English which contains various theories in it. Media that is considered attractive for teaching this material is vlogs. A vlog is a video uploaded by someone on YouTube so that anyone can see it anytime and anywhere as long as they have an internet connection to access it. Students are able to watch the explanation of the material repeatedly so that they become increasingly aware of the material. This research is using experimental method. Before the research was carried out, the sample was determined to be the subject of this study. After the sample is obtained, the researcher tests the research instrument to find out whether the instrument is valid and reliable or not. Furthermore, pre and post tests were carried out to collect research data. Data were analyzed with statistics and then conclusions were drawn.